2004
DOI: 10.1152/ajpheart.00822.2003
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dimethylarginine upregulates LOX-1 in activated macrophages: role in foam cell formation

Abstract: Intimal infiltration by monocytes and accumulation of lipids represent a critical step in the formation of fatty streaks during atherogenesis. Because elevated plasma levels of asymmetric dimethylarginine (ADMA), a potent nitric oxide (NO) synthase (NOS) inhibitor, are prevalent in diverse cardiovascular diseases, the goal of this study was to examine the contribution of NO deficiency to macrophage lipid accumulation. Inhibition of NO synthesis in PMA-primed human monocytic leukemia HL-60 cells resulted in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 61 publications
1
52
1
2
Order By: Relevance
“…In renal failure, ADMA accumulation only in part depends on compromised excretory function in that it was shown that reduced dimethylarginine dimethylaminohydrolase activity may contribute substantially to ADMA accumulation (29). The wide-range involvement of ADMA in the atherosclerosis process is epitomized by recent in vitro findings indicating that ADMA contributes to macrophage lipid accumulation, which is a critical step in the formation of fatty streaks during atherogenesis (30). In this cohort, the vast majority of deaths (61%) were cardiovascular in nature.…”
Section: Discussionmentioning
confidence: 99%
“…In renal failure, ADMA accumulation only in part depends on compromised excretory function in that it was shown that reduced dimethylarginine dimethylaminohydrolase activity may contribute substantially to ADMA accumulation (29). The wide-range involvement of ADMA in the atherosclerosis process is epitomized by recent in vitro findings indicating that ADMA contributes to macrophage lipid accumulation, which is a critical step in the formation of fatty streaks during atherogenesis (30). In this cohort, the vast majority of deaths (61%) were cardiovascular in nature.…”
Section: Discussionmentioning
confidence: 99%
“…6) Recent studies with cultured cells suggest that LOX-1 may play several important roles in destabilization of atherosclerotic plaques, inducing expression of adhesion molecules and chemokines for monocytes, 7) transformation of macrophages into foam cells, 8,9) apoptosis of smooth muscle cells 10,11) and the degradation of extracellular matrix proteins by induction of matrix metalloproteinases.…”
Section: )mentioning
confidence: 99%
“…3) Lectin-like oxidized low density lipoprotein (LDL) receptor-1 (LOX-1), a type II membrane glycoprotein belonging to the C-type lectin family, acts as a cell-surface receptor for oxidized LDL (Ox-LDL) and mediates several biological effects of Ox-LDL. 6) Recent studies with cultured cells suggest that LOX-1 may play several important roles in destabilization of atherosclerotic plaques, inducing expression of adhesion molecules and chemokines for monocytes, 7) transformation of macrophages into foam cells, 8,9) apoptosis of smooth muscle cells 10,11) and the degradation of extracellular matrix proteins by induction of matrix metalloproteinases.…”
mentioning
confidence: 99%
“…e involvement of LOX-1 in the development of atherosclerosis resulting from MetS has been suggested by the fact that the cardiovascular risk factors of MetS are closely associated with the upregulation of LOX-1. Dyslipidemia, particularly increased plasma level of ox-LDL, plays the major role in the upregulation of LOX- [27], and production of matrix metalloproteinases [28], resulting in cell injury that facilitates atherosclerotic plaque formation and progression. Our results suggest that LOX-1 plays a pivotal role in the cross-talk between MetS and CAD, and high sLOX-1 level could perhaps be used to predict the occurrence of future cardiovascular events in patients with MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also found that circulating levels of sLOX-1 are signi cantly increased in metabolic disorders, including obesity [11] and type 2 DM [12], and are positively correlated with reduction in body weight [13]. e activation of LOX-1 is involved in endothelial ECs dysfunction [25], apoptosis of VSMCs [26], accumulation of lipids in macrophages [27], and production of matrix metalloproteinases [28], resulting in cell injury that facilitates atherosclerotic plaque formation and progression. Our results suggest that LOX-1 plays a pivotal role in the cross-talk between MetS and CAD, and high sLOX-1 level could perhaps be used to predict the occurrence of future cardiovascular events in patients with MetS.…”
Section: Discussionmentioning
confidence: 99%